Report on a journey from Maidugari, Nigeria to Jeddah in Arabia - Palmer, H. R. (Adam Matthew Digital, 1919)
Report to the Colonial Office on a journey from Maidugari (Bornu Province, Nigeria) to Jeddah via Baghermi, Wadai, Darfur, Senaar, Khartoum and Suwakim between 1 Nov. 1918 and 15 Apr. 1919; includes general remarks on the Pilgrim Route from Maidugari to Jeddah, Fellata pilgrims, commercial conditions and political notes